2018
DOI: 10.1111/aor.13106
|View full text |Cite
|
Sign up to set email alerts
|

Design of Bioartificial Pancreases From the Standpoint of Oxygen Supply

Abstract: A bioartificial pancreas (BAP), in which islets of Langerhans (islets) are enclosed in a semipermeable membrane, has been developed to realize islet transplantation without the use of immunosuppressive drugs. Although recent progress in induced pluripotent stem (iPS) and embryonic stem (ES) cells has attracted attention owing to the potential applications of these cells as insulin-releasing cells, concerns about the safety of implantation of these cells remain. The use of the BAP has the advantage of easy remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Iwata et al. focused on the oxygen diffusion in a device and indicated that spherical bioartificial pancreas allows for selecting a wider range of membrane thicknesses than cylindrical and planar ones [14]. We didn't find any central necrosis, one sign of hypoxia, in the encapsulated spheroids, suggesting that a minimal oxygen concentration was maintained.…”
Section: Discussionmentioning
confidence: 64%
“…Iwata et al. focused on the oxygen diffusion in a device and indicated that spherical bioartificial pancreas allows for selecting a wider range of membrane thicknesses than cylindrical and planar ones [14]. We didn't find any central necrosis, one sign of hypoxia, in the encapsulated spheroids, suggesting that a minimal oxygen concentration was maintained.…”
Section: Discussionmentioning
confidence: 64%
“…Spherical microcapsules, for example, typically feature diameters ranging from 250 μm to 1500 μm [16,254,297]; however, theoretical analyses of physiological oxygen transport suggest that the thickness of a spherical microcapsule should be controlled below 100 μm to avoid central islet hypoxia and necrosis in common transplantation sites [298]. Buchwald et al also demonstrated that 1800 μm-diameter microspheres delay and reduce insulin secretion as a result of the large distance which must be traversed by passive diffusion [129].…”
Section: Nanoencapsulationmentioning
confidence: 99%
“…Hiroo Iwata et al of RIKEN, Kobe, Japan, reported on their continuing research on a bioartificial pancreas (BAP). They derived several equations considering oxygen supply in BAPs in order to provide insights into the rational design of three different types of BAPs (spherical microcapsules, cylindrical capsules, and planar capsules).…”
Section: Pancreatic Supportmentioning
confidence: 99%